1995
DOI: 10.2190/lhkx-qyh0-2j42-mnc2
|View full text |Cite
|
Sign up to set email alerts
|

Life after the Death of a Child: Initial and Long Term Support from Others

Abstract: This article presents research on both the source and continuity of support received by bereaved parent(s) within four different social contexts: family, friends, co-workers, and clergy. The data were obtained from a study conducted in 1990–91 on the social impact of the death of a child, and are drawn from fourteen interviews with bereaved parents representing nine families and ten child deaths. The responses to three questions are considered. First, how were you treated by family members and close friends? W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 5 publications
3
30
0
Order By: Relevance
“…Bereaved individuals may not receive support from friends and family members simply because these individuals are also grieving (Brabant, Forsyth, & McFarlain, 1995). Moreover, the support offered to bereaved parents may be short-lived and not sustained for long periods of time (Brabant et al, 1995).…”
mentioning
confidence: 99%
“…Bereaved individuals may not receive support from friends and family members simply because these individuals are also grieving (Brabant, Forsyth, & McFarlain, 1995). Moreover, the support offered to bereaved parents may be short-lived and not sustained for long periods of time (Brabant et al, 1995).…”
mentioning
confidence: 99%
“…This style of support is low cost and easily accessible (Van der Houwenet al Within this category, groups that have a focus on child death comprise 23% of all mourning and loss groups, suggesting that parents who have lost a child may need support for longer than other bereavement situations and that other support networks may tire of giving their support over a lengthy period. This is consistent with other research which suggests family and community tend to place a judgment on how long a person should mourn for their child before they start to 'get on with life' (Murphy 1990;Brabant, Forsyth, McFarlan 1995;Breen, O'Connor 2011). Online support offers additional support for bereaved people and is not a substitute for other forms of support Van der Heuwen et al 2010.…”
Section: Online Support -Beyond Time Financial and Geographical Conssupporting
confidence: 85%
“…Brabant et al studied parents who had lost their child and were members of the Compassionate Friends USA 5 (Brabant, Forsyth, McFarlan 1995). Although this sample may have biased the study cohort as the parents were obviously seeking additional support not evidenced within their social structure, Brabant examined parents' experiences within four social contexts: clergy, family, friends and co-workers.…”
Section: Social Supports and Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…The communication among bereaved parents post-loss is a primary ways of meaning -making (Bosticco & Thompson, 2005;Sedney, Baker, & Gross, 1994). However, after the death of a child, communication can be difficult (Brabant, Forsyth, & McFarlain, 1995;Hastings, 2000). Studies on spousal communication after the death of a child that involved Weterners Parents concluded that havingcomplete openness dialogues and the ability to grief together is described as good and healthy relationship (Baxter & Montgomery, 1996).…”
Section: Communication After the Death Of A Childmentioning
confidence: 99%